A computational analysis of lexical elaboration across languages - Temuulen Khishigsuren; Terry Regier; Ekaterina Vylomova; Charles Kemp (Proceedings of the National Academy of Sciences, 2025)
Claims about lexical elaboration (e.g. Mongolian has many horse-related terms) are widespread in the scholarly and popular literature. Here, we show that computational analyses of bilingual dictionaries can be used to test claims about lexical elaboration at scale. We validate our approach by introducing BILA, a dataset including 1,574 bilingual dictionaries, and showing that it confirms 147 out of 163 previous claims from the literature. We then identify previously unreported examples of lexical elaboration, and analyze how lexical elaboration is influenced by ecological and cultural variables. Claims about lexical elaboration are sometimes dismissed as either obvious or fanciful, but our work suggests that large-scale computational approaches to the topic can produce nonobvious and well-grounded insights into language and culture.